Growth, exclusion and vulnerability: evaluation of the socio-spatial transformation of post-apartheid Pretoria-Tshwane (South Africa) - Andre Horn (Boletín de la Asociación de Geógrafos Españoles)
Apartheid left South African city regions with two major challenges: social integration at a city level and spatial integration at a regional level. The task to finds solutions to these problems was left to municipalities, the lowest level of the three trier government system introduced after 1994. This article critically evaluates the success of the post-apartheid municipal government of Pretoria-Tshwane to address the said challenges in the reorganization of the city region over a 25-year period. The paper starts with a reconstruction of the apartheid city to display its socio-spatial contrasts and to define the challenge of integration and compaction. The investigation is based on literature, census information and observation. The main finding is that the progress made with the integration of the city at both scales is being neutralized by demographic trends, choice of association, urban sprawl, uncertain management, the scale of aspirations, unrealistic expectations and, most of all, municipal incapacity. The failure of the local government of Pretoria-Tshwane to achieve the said goals points to the inefficiency of the current approach that obligates municipalities with the complete task to rectify the dichotomies of the apartheid city system within their regions.  It is advocated that additional governmental entities be implemented to support local governments with the planning and re-development of post-apartheid city-regions.